The expression of emotional skills among individual and team sports male athletes - A.V. Akelaitis; R.K. Malinauskas (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Athlete must recognize and manage one's emotions, as well as their opponents and teammates emotions, in order to perform well in sports. For athletes, higher emotional skills have been linked to higher performance in sports. Purpose: to reveal the peculiarities of the expression of emotional skills among individual and team sports male athletes. Material: the participants comprised of 204 individual sports (track and field athletes, gymnasts, swimmers, badminton players, table tennis players, bodybuilders, and cyclists) and 212 team sports (basketball, football, volleyball, handball, and rugby players) male athletes from Lithuanian sport clubs/schools, age ranged 15 to 18 years old. The measures of emotional skills were evaluated using Social Emotional School Readiness Scale (BUSSE-SR), Rosenberg Self-Esteem Scale, and Emotional Intelligence Questionnaire - Short Form (TEIQue - SF). In order to analyse data, descriptive statistics (mean, standard deviation), Student's t test, and Cohen's d were utilized. Results: the comparison of the expression of emotional skills among individual and team sports male athletes revealed that team sports male athletes have higher rate of self-awareness and self-regulation skills than individual sports male athletes (p < .05). Meanwhile, Student's t test for independent samples showed that there no significant differences between individual and team sports male athletes in terms of their abilities to express emotions, and self-esteem skills (p > .05). Conclusions: the findings of the quantitative study confirmed our research hypothesis that male athletes who compete in team sports will have more developed emotional skills than those in individual sports: team sports male athletes have more developed self-awareness and self-regulation skills than individual sports male athletes.